Development of a Learning Unit Design for Environmentally Friendly Energy Sources Based on the Utilization of Palm Oil Waste Briquettes - Fitri Mulyani*; Bhakti Karyadi; Mellyta Uliyandari; Ariefa Primair Yani; Rendy Wikrama Wardana; Sausan Fatin Nurazizah; Lasriani Lasriani (JIPI (Jurnal IPA dan Pembelajaran IPA), 2023)
Palm shell waste and empty palm fruit bunches thrown away can cause environmental pollution. This palm oil waste can be used as an environmentally friendly energy source, namely briquettes. Briquettes, as an environmentally friendly energy source, can be used as teaching material in school science learning. This study aims to design learning units for environmentally friendly energy sources based on palm shell waste briquettes and empty palm fruit bunches as teaching materials. Data collection techniques were carried out by observing the potential of palm oil waste in the North Bengkulu area and need analysis, including material analysis and interviews. The resulting analytical data were analyzed descriptively regarding the composition, texture, colour, test of briquettes used, burning time, calorific value and moisture content of the resulting briquettes. The sample of needs analysis data collection was determined by purposive sampling. The data from the analysis will be developed into teaching materials packaged in designing learning units on environmentally friendly technology materials for junior high school students